Detection of Avian Leukosis Virus Subgroup J in Egyptian Ducks and Chicken Using Molecular and Histopathological Approach and Allocation of Genetic Mutations and Recombination Events in the Envelope Protein Gene gp85 - Soliman, Yousef A.; Gamal, Maha A.N.; El-Nagar, Eman M.S.; Khattab, Marwa S.; Salem, Heba M. (Journal of Advanced Veterinary Research, 2023)
Avian leukosis virus (ALV) is an oncogenic contagious virus infecting different avian species. This study aims to molecularly detect the circulating strains of ALV in various chicken and duck farms at different Egyptian governorates. Freshly dead birds were exposed for postmortem examination (PM) then samples were processed for histopathological examination as well as molecular detection of ALV using qRT-PCR and sequence analysis of the envelope glycoprotein gene (gp85) surface protein antigen with detection of recombination events that might be found between the detected strains. PM revealed the existence of diffuse enlargement of most internal organs, and in some cases, nodular enlargement was observed. Histopathological investigation showed myeloid cells infiltration of eosinophilic granular cytoplasm in the examined tissues. Five molecularly positive samples were sequenced and submitted in the GenBank with accession numbers MZ614719, MZ614720, MZ614721, MZ614722, and MZ614723. The phylogenetic tree construction based on the sequenced gp85 gene revealed that all Egyptian isolates were nearly arranged in a single branch despite the year of collection and were phylogenetically distant from other sequences. In general, studies concerning the genetic diversity of gp85, and the recombination events concluded that the ALV-J virus is a wide host range involving both chicken and ducks. Because ALV causes serious financial problems to threaten poultry production and neither vaccines nor treatment tools are now available for ALV prevention and control, periodical molecular monitoring with whole genome sequence and analysis for the circulating strains with ethical eradication of the positive birds are recommended to overcome such a problem.